Media Indonesia Marketing Strategy to Incrase Their Gen Y Readers - Asril, Abrar; Hudrasyah, Herry (The Indonesian Journal of Business Administration, 2013)
Since Gen Y is the biggest population in Indonesia, Gen Y were also being the most potential market for Media Indonesia to increase their readership. To fit their newspaper for the Gen Y crowd, Media Indonesia should do several things. They should understand about Gen Y, know their needs, and choose a marketing strategy that fit the Gen Y as their target market. This research was collected from a survey of 170 respondents with a characteristic age around 14-35, living in DKI Jakarta, familiar with newspapers, familiar with the internet, and with minimal Senior High School educational background. This research also conducted an interview with the Media Indonesia Business Development General Manager and Media Indonesia readers. This research found that Content, Cover & Layout, and Brand being factors that raises the Gen Y interest in reading a newspaper. This research also found the favorite contents of Gen Y are Sports, Technology, Music & Film, Economy, and Communities. To maintain and increase readership of their Gen Y readers, Media Indonesia shall set up their marketing strategy that fit the Gen Y group. This marketing strategy is set up for 5 years with a target to increase the total readership of their Gen Y demographic. The recommendation here is that Media Indonesia shall improve their content, cover & layout, and their brand to fit for the Gen Y group. After doing some improvement of their newspaper, they recommended to apply a new wave of marketing strategy to get the attention of the Gen Y group. The new wave marketing mix of strategies that was suggested is co creation, communal activation, conversation, and commercialization.